Correction: Self-monitored photothermal nanoparticles based on core–shell engineering. Issue 13 (10th March 2016) - Ximendes, Erving C.; Rocha, Uéslen; Jacinto, Carlos; Kumar, Kagola Upendra; Bravo, David; López, Fernando J.; Rodríguez, Emma Martín; García-Solé, José; Jaque, Daniel
Abstract : Correction for 'Self-monitored photothermal nanoparticles based on core–shell engineering' by Erving C. Ximendes et al., Nanoscale, 2016, 8, 3057–3066.